Heritability and Evolutionary Potential Drive Cold Hardiness in the Overwintering Ophraella communa Beetles - Zhao, Chenchen; Ma, Fangzhou; Chen, Hongsong; Wan, Fanghao; Guo, Jianying; Zhou, Zhongshi (Frontiers in Physiology, 2018)
Chill tolerance plays a crucial role that allows insect species to adapt to cold environments. Two Chinese geographical populations (Laibin and Yangzhou populations) were selected to understand the chill resistance and evolutionary potential in the Ophraella communa, a biological control agent of the invasive common ragweed, Ambrosia artemisiifolia. Super-cooling point assays, knockdown tests under static low-temperature conditions and determination of glycerol content were studied. ANOVAs indicated significant differences regarding chill coma recovery time, super-cooling point and glycerol content across populations and sexes. The narrow-sense heritability (h2) estimates of cold resistance based on a parental half-sibling breeding design ranged from 0.39 to 0.53, and the h2 value was significantly higher in the Yangzhou population than in the Laibin population. Additive genetic variances were significantly different from zero for cold tolerance. The Yangzhou population of O. communa has a strong capability to quickly gain resistance to cold. We conclude that the O. communa beetle has a the plasticity that can provide cold resistance in the changing climate conditions.